2020
DOI: 10.1097/mca.0000000000001002
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine variation improves Zwolle score in selecting low-risk patients after ST-segment elevation myocardial infarction

Abstract: Background The Zwolle score is recommended to identify ST-segment elevation myocardial infarction (STEMI) patients with low-risk eligible for early discharge. Our aim was to ascertain if creatinine variation (Δ-sCr) would improve Zwolle score in the decision-making of early discharge after primary percutaneous coronary intervention (PCI). Methods and results A total of 3296 patients with STEMI that underwent primary PCI were gathered from the Portuguese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…example, Lim et al demonstrated that Zwolle score stratification could identify low-risk patients for early discharge(35). However, some studies(36,37) have shown that adding creatinine, BNP, and proBNP variables can improve the value of this score in identifying low-risk patients for early discharge. At the same…”
mentioning
confidence: 99%
“…example, Lim et al demonstrated that Zwolle score stratification could identify low-risk patients for early discharge(35). However, some studies(36,37) have shown that adding creatinine, BNP, and proBNP variables can improve the value of this score in identifying low-risk patients for early discharge. At the same…”
mentioning
confidence: 99%